Character Values In Physical Education At MIS Nurul Ulum In Talang Pauh Village, Central Bengkulu - Ajis Sumantri; Hermansyah Hermansyah (Sinar Sport Journal, 2023)
The research aims to find out the application of physical education character values and to find out the obstacles in implementing physical education character values in Bengkulu City 89 Elementary School. The research design uses a descriptive with a qualitative approach. Data collection through interviews, 4 informants. Data analysis through the stages of reduction, data display and conclusion. The results of the study found that the application of physical education character values to the character of respect was not very good, there were some students who did not respect their opponents, sometimes yelling at their opponents. Students also have no respect in accepting defeat. Then the character of responsibility is good enough, students are ready if there is sports practice at school, when playing games students are seen working together with their friends. However, there are some students who are not disciplined in practice. Furthermore, the character of caring is good enough, students have high concern for helping friends to play better, provide assistance when there are friends who have problems, students also play in teams. However, there was still a lack of concern about giving praise, students did not dare to express praise to their friends who played better. Honest character is high, students comply with the rules of the game and admit when they make mistakes. Fair character is not that good, there are a small number of students who are not fair to their friends, especially in determining playgroups which tend to be based on physical and economic background. Civilized character is already good, students can be an example and try to achieve the best. The relevance of the aspects of physical education character values with school learning plans is only the character of responsibility that is relevant. For caring, honest and fair characters, they are only partially relevant, while for respect and civilized characters, they are irrelevant.